2019
DOI: 10.12659/msm.913506
|View full text |Cite
|
Sign up to set email alerts
|

Serum Triglycerides Are Related to Chronic Kidney Disease (CKD) Stage 2 in Young and Middle-Aged Chinese Individuals During Routine Health Examination

Abstract: Background The aim of this study was to determine the risk factors for early chronic kidney disease (CKD) (GFR 60–89 ml/min/1.73 m 2 ; CKD stage 2) in asymptomatic Chinese individuals undergoing routine health examination. Material/Methods This cross-sectional study enrolled 9100 individuals who received voluntary medical examinations between 10/01/2011 and 09/30/2017. Demographic data, clinical history, clinical examination, medication, smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The findings of the albumin (ALB) and fasting glucose level (GLU) are consistent with previous studies following Korbut et al [ 36 ] and Kshirsagar et al [ 37 ]. Similarly, Xue et al [ 38 ], Mahmood et al [ 39 ], and Kshirsagar et al [ 37 ] reported that triglycerides (TG), age, and gender are critical for prediction of chronic kidney disease. As suggested from our results, the main issue is how to predict CKD who are asymptomatic and who only undergo a routine adult health examination program.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the albumin (ALB) and fasting glucose level (GLU) are consistent with previous studies following Korbut et al [ 36 ] and Kshirsagar et al [ 37 ]. Similarly, Xue et al [ 38 ], Mahmood et al [ 39 ], and Kshirsagar et al [ 37 ] reported that triglycerides (TG), age, and gender are critical for prediction of chronic kidney disease. As suggested from our results, the main issue is how to predict CKD who are asymptomatic and who only undergo a routine adult health examination program.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed out that lipids and apolipoproteins can be involved in the occurrence and development of renal diseases, such as chronic kidney disease and renal calculus. [13][14][15][16] Furthermore, a large population-based retrospective analysis has also indicated that higher serum TG levels in men are associated with a significant increase in the risk of kidney cancer. 17 An important histological feature of renal clear cell carcinoma is lipid droplet structures with large TG and other substances.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between changes in serum lipid levels and changes in kidney disease have generally been found in observational studies. Several studies have pointed out that lipids and apolipoproteins can be involved in the occurrence and development of renal diseases, such as chronic kidney disease and renal calculus 13‐16 . Furthermore, a large population‐based retrospective analysis has also indicated that higher serum TG levels in men are associated with a significant increase in the risk of kidney cancer 17 .…”
Section: Introductionmentioning
confidence: 99%